The ‘Autobiography’ of Tippu Tip: Geography, Genre and the African Indian Ocean - Decker, Michelle (Interventions, 2015)
Keywords: Tippo Tip (1837-1905); Zanzibar

ʿUmānī fī ‘l-Sharq al-Ifrīqī: ‟Tībū Tībˮ Nāẓiran wa-Manẓūran ilayhi - Saʿīdī, Aḥmad al- (al-Mu’tamar al-Duwalī : al-Dawr al-ʿUmānī fī ‘l-Sharq al-Ifrīqī, 11-13 Dec. 2012. Buḥūth al-Mu’tamar, 2014)
Keywords: Tippo Tip (1837-1905)

Stuart Laing. Tippu Tip: Ivory, Slavery and Discovery in the Scramble for Africa - Kyle, Michael (Asian Affairs, 2018)
Keywords: Esclavage – Zanzibar; Recension; Tippo Tip (1837-1905)

The Life of Tippu Tip. Tippu Tip: Ivory, Slavery, and Discovery in the Scramble for Africa - Mathews, Nathaniel (The Journal of African History, 2019)
Keywords: Esclavage – Zanzibar; Recension; Tippo Tip (1837-1905)

Tippu Tip: ivory, slavery and discovery in the scramble for Africa - Laing, Stuart (Medina Publishing Ltd, 2017)
Tippu Tip, notorious to some, intriguing to others, was a Zanzibari Arab trader living in the turbulent and rapidly changing Africa of the late 19th century. This biography transports the reader into his extraordinary world, describing its exotic cast of characters and the principal factors that shaped it. His colorful life culminated in his engagement as governor of a province in the 'Congo Free State' of the Belgian King Leopold, and in his involvement in Stanley's astonishing expedition to relieve Emin Pasha, governor of the Egyptian southern province of Equatoria. This book is the first thorough investigation in English of this significant figure. The lucid narrative unfolds against the political and economic backdrop of European and American commercial aims, while allowing the reader to see the period through African and Arab eyes. The fascinating figures who strutted the 19th-century African stage, and their hardly believable exploits, give this book an appeal reaching beyond the African specialist to the general reader
Keywords: Esclavage – Zanzibar; Tippo Tip (1837-1905)